Quantifying the yield gap minimization in lentil (Lens culinaris) under Cluster Frontline Demonstrations (CFLD) conducted in Uttar Pradesh - DUBEY, SHANTANU KUMAR; GAUTAM, U S; SINGH, A K; SINGH, ATAR; CHAHAL, V P; SINGH, AVNISH KUMAR; SINGH, CHANDAN; SRIVASTAVA, AJIT (The Indian Journal of Agricultural Sciences, 2018)
On-farm cluster front line demonstrations were conducted for lentil crop across the nine districts of Eastern Plain Zone (Faizabad, Barabanki, Sultanpur, Azamgarh, Ballia, Chandauli, Mau, Gazipur and Jaunpur) and six districts of Bundelkhand Zone (Jhansi, Lalitpur, Hamirpur, Banda, Jaloun and Chitrakoot) of Uttar Pradesh during rabi season of (2015- 16) in Indian sub-continent. In Eastern Plain Zone an area of 120 ha and in Bundelkhand zone 230 ha area each with plot size of 0.40 ha (1 acre) were included under these demonstrations with active participation of 930 farmers from both the zones. Data were analyzed in terms of yield gap, yield advantages and yield gap minimized for district level, state level and potential yield level of winter pulse crop lentil (Lens culinaris L.). The profitability analysis was also done for these demonstrations. The district level yield gap was computed highest in Bundelkhand (133-296%) followed by in the districts of eastern plain zone (128-158%). The obtained yield advantages helped to minimize the extension gap to maximum extent in districts of eastern plain zone (43-66%). Similar trend was observed in state level yield gap minimization (%) in both the zones of Uttar Pradesh. The potential yield gap minimized (%) at farmer level through demonstration of lentil was computed to be higher (31-52%) for most (3) of the districts of Bundelkhand and remaining districts (2) could witness 15 to 30 percent yield gap minimization except for Banda (7.64%) whereas in other districts of eastern plain zone, the potential yield gap could be minimized only to the extent of 5.43 to 15.43% and for the district Jaunpur, the gap was minimized to as lower extent as 1.62%. The major economic indicators like gross cost (Rupees/ha), gross return (Rupees/ha), net return (Rupees/ha), and B:C ratio were computed both for farmers field and demonstrated plot. The percentage increase in net return over farmers’ existing plot and demonstration plot was highest in the district of Mau (219.27%), Sultanpur (115.70%), Jhansi (110.34%), Faizabad (105.57%) and other districts ranged from 18.29 to 88.12% in both the zones of Uttar Pradesh. The above study is, thus, the indicated the practical implications and usability of CFLD in minimizing the yield gap of lentil at the farmersâ€™ fields..